Bulk and amino acid isotope evidence of supplementary food sources besides euphotic production for a deep-sea coral community in the South China Sea - Luo, Zhongyuan; Chen, Lingdi; Jia, Guodong (Frontiers in Marine Science, 2024)
Deep-sea coral communities, rich in various zoobenthos, have been discovered in the South China Sea (SCS) in recent years. Yet little is known about the trophic structure of these communities. In this study, we applied bulk isotope and compound-specific isotope analysis of amino acids (CSIA-AAs) to explore feeding strategies and estimate the trophic positions (TPs) and isotopic baseline for 6 deep-sea gorgonians and 7 other zoobenthos collected from a deep-sea coral community in the SCS. Bulk carbon and nitrogen isotope values (δ 13 C and δ 15 N) suggested that the zoobenthos in the community have a variety of food sources. Amino acids δ 15 N results indicated that the TP is 2.3 ± 0.2 (mean ± 1σ) for the deep-sea gorgonians and varies from 2.0 ± 0.3 (sponge) to 3.5 ± 0.5 (starfish) for other zoobenthos. The δ 15 N values of phenylalanine revealed variable isotopic baselines ranging from +3.0 ± 0.9‰ to +11.7 ± 0.5‰, reflecting the incorporation of nitrogen from sources not limited to surface primary producers. Taken together, our data suggest that zoobenthos in the deep-sea coral community are mostly omnivorous, and their diet does not come solely from export production from the sea surface, with symbiotic bacteria as a potential important source.